Competence-based learning in engineering mechanics in an adaptive online learning environment. (10th August 2018) - Linke, Markus; Landenfeld, Karin
Abstract: In engineering sciences like mechanical or automotive engineering, pre-knowledge in mathematics is required to follow deeply specific engineering lectures. Mathematical skills are essential preconditions to successfully complete engineering lectures. It is necessary that these preconditions are identified for each individual student so that suitable learning opportunities can be provided according to the individual student needs. Within this paper an approach of competence-based learning in engineering mechanics is presented. This approach is assisted by an online learning environment that is adapted and extended by several features in order to enable a competence-oriented learning strategy. Computer-assisted tests are used for measuring mathematical pre-knowledge and pre-skills. Moreover, a mastery learning approach based on exercises is utilized in order to secure a certain skill level before students move forward to learn subsequent competencies. Test results influence the individual learning path by offering different learning elements to each student.